Factors Influencing Classroom Management Ability among Teachers in Islamic Integrated School - Fatriani, Fatriani; Masbirorotni, Masbirorotni; M. Rd. Ali, M. Rd. Ali (FKIP Universitas Jambi, 2026)
Classroom management ability is a fundamental competency that determines the effectiveness of teaching and learning processes in primary education. However, variations in teachers’ classroom management skills remain a challenge, particularly in Islamic integrated elementary schools that emphasize both pedagogical competence and character development. This study examined the simultaneous and partial effects of teaching experience, educational background, and teacher personality on classroom management ability among teachers at SDIT Ash-Shiddiiqi Jambi City. Using a quantitative explanatory survey design, data were collected from a saturation sample of 99 teachers through structured Likert-scale questionnaires. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that teaching experience, educational background, and teacher personality jointly explained 66.6% of the variance in classroom management ability (R2=0.666R^2 = 0.666R2=0.666). Teacher personality had the strongest and statistically significant effect (β = 0.630, p < 0.001; f2=0.649f^2 = 0.649f2=0.649), followed by educational background (β = 0.214, p < 0.001; f2=0.097f^2 = 0.097f2=0.097). In contrast, teaching experience did not significantly influence classroom management ability (β = 0.082, p = 0.268; f2=0.011f^2 = 0.011f2=0.011). These findings suggest that personality-related attributes contribute more substantially to effective classroom management than teaching experience within the context of this study. Therefore, teacher development programs in Islamic elementary schools should place greater emphasis on personality development, reflective professional learning, and holistic teacher recruitment practices to enhance educational quality.